Multi-Beam Focusing and Deflecting Characteristics of Liquid Crystal Optical Phased Array - Xue Xu; Lin Xu; Xitong Liang; Jun Dai (Photonics)
As a programmable optical device, a liquid crystal optical phased array (LCOPA) has many unique applications. Multi-beam fan-out is one of the novel application cases. However, currently commercially available liquid crystal optical phased array devices typically use reflective structures and are operated on desktop software. This can be inconvenient for the construction of the optical path and the manipulation of the device. On the other hand, multi-beam fan-out capability alone may not be sufficient in some application scenarios. The additional function of focusing might bring some new advantages. Thus, we developed a transmissive liquid crystal optical phased array device based on a fully embedded human–computer interaction control method. It does not require the installation of computer desktop software and only needs a touch screen for easy human–computer interaction. This not only brings convenience to control, but also reduces the cost of devices. Meanwhile, based on the Gerchberg–Saxton algorithm (GS algorithm) and the method of lens phase superposition, we achieved a composite function of multiple-beam fan-out with focusing function by simulation and experiment. This composite function may have unique application value for some special application scenarios.